Development and survival of nymphs of Podisus nigrispinus (Heteroptera: Pentatomidae) fed with caterpillars of Chlosyne lacinia saundersii (Lepidoptera: Nymphalidae) - Silva,Carlos Alberto Domingues da (2009)
The development and survival of Podisus nigrispinus (Dallas) (Heteroptera: Pentatomidae) nymphs fed on larvae of Chlosyne lacinia saundersii Doubleday & Hewitson (Lepidoptera: Nymphalidae) was studied at 25 ± 1ºC, 68 ± 10% relative humidity and 12 h photo phase. P. nigrispinus developed until the adult stage when fed on C. lacinia saundersii caterpillars. However, the survival rate of P. nigrispinus during early instars allowed this predator to complement its diet with other preys and to maintain its populations in areas with the sunflower culture.